METABOLIC EFFECTS OF FEEDING DIFFERENT SOURCES OF SUPPLEMENTAL FAT TO LACTATING NILI-RAVI BUFFALOES - H. Nawaz; M. Abdullah M. Yaqoob; M. E. Babar; M. A. Jabbar; M. Tariq (Journal of Animal and Plant Sciences, 2012)
Four early lactating Nili-Ravi buffaloes were fed four diets either contained no added fat or had tallow, poultry fat or mustard oil at 3% of dietary dry matter in an experiment conducted in a 4x4 Latin square design. Intakes of DM, OM, CP, ADF and NDF decreased in buffaloes fed supplemental tallow or poultry fat than those fed control diet or diet containing mustard oil. Intake of EE increased due to supplemental fats and oil. Intakes of NEL and DE were higher in buffaloes fed mustard oil versus those on control, tallow or poultry fat. Dietary tallow increased DM digestibility than the control diet. Digestibility of EE increased in buffaloes fed diets containing tallow and poultry fat versus those on control or mustard oil. Rumen pH did not differ, whereas, acetate to propionate ratios were lower due to different fat sources than the control diet. Mustard oil supplemented diet increased butyrate content. Blood pH, concentrations of glucose, total cholesterol, triglycerides and total blood lipids did not vary significantly due to feeding different fat sources. It was concluded that fat sources studied can be fed safely at 3% of dietary dry matter to early lactating Nili- Ravi buffaloes
Keywords: Fat sources; buffalo; digestibility; rumen fermentation; blood metabolites